Teaching Listening By Using English Pop Song - Rusmiati, Rusmiati; Dewi, Siti Rahma (STKIP Bina Bangsa Getsempena Banda Aceh, 2015)
This thesis entitled, âTeaching Listening By Using English Pop Song (an experimental teaching to second grade of SMP Negeri 17 Banda Aceh)â. The purpose of this study is to find out the problem faced by studentsâ in listening, and to know the improvement of studentsâ listening. To find data and information in the field, the writer conducted the research at SMP Negeri 17 Banda Aceh. The participants were the second grade students which was about 28 studentsâ. The writer collected some theories and opinions of expert from different resources to support this thesis. The writer also used some techniques in the data collecting process, such as questioner and experimental teaching. the data analysis of experiment group were 59,5 for pre test, and post-test 86,10. So, it can be concluded that Teaching listening by using English pop song is effective and can improve students ability listening.Key Word: Listening English Pop Song